Water quality and quantity investigation of green roofs in a dry climate. (1st March 2015) - Beecham, S.; Razzaghmanesh, M.
Abstract: Low-energy pollutant removal strategies are now being sought for water sensitive urban design. This paper describes investigations into the water quality and quantity of sixteen, low-maintenance and unfertilized intensive and extensive green roof beds. The factors of Slope (1° and 25°), Depth (100 mm and 300 mm), Growing media (type A, type B and type C) and Species (P1, P2 and P3) were randomized according to a split–split plot design. This consisted of twelve vegetated green roof beds and four non-vegetated beds as controls. Stormwater runoff was collected from drainage points that were installed in each area. Samples of run-off were collected for five rainfall events and analysed for water retention capacity and the water quality parameters of NO2, NO3, NH4, PO4, pH, EC, TDS, Turbidity, Na, Ca, Mg and K. The results indicated significant differences in terms of stormwater water quality and quantity between the outflows of vegetated and non-vegetated systems. The water retention was between 51% and 96% and this range was attributed to the green roof configurations in the experiment. Comparing the quality of rainfall as inflow, and the quality of runoff from the systems showed that green roofs generally acted as a source of pollutants in this study. In the vegetated beds, the intensive green roofs performed better than the extensive beds with regard to outflow quality while in the non-vegetated beds, the extensive beds performed better than intensive systems. This highlights the importance of vegetation in improving water retention capacity as well as the role of vegetation in enhancing pollutant removal in green roof systems. In addition growing media with less organic matter had better water quality performance. Comparison of these results with national and international standards for water reuse confirmed that the green roof outflow was suitable for non-potable uses such as landscape irrigation and toilet flushing. Highlights: Outflows from twelve vegetated and four non-vegetated green roofs were studied. Water retention was higher in vegetated beds than in non-vegetated. Both vegetated and non-vegetated systems acted as pollutant sources. The media containing higher organic content generated higher nutrient concentrations. Standards indicate that such water can be reused for urban landscape irrigation.